Quotas : Updated Calculations and Quota Variables. (Policy Papers; Policy Paper ;, 2009)
In its April 2009 Communique, the IMFC called for a prompt start to the Fourteenth General Review of Quotas so that it is completed by January 2011--some two years ahead of schedule. The IMFC noted that the review is expected to result in increases in the quota shares of dynamic economies, particularly in the share of emerging market and developing countries as a whole. The IMFC also looked forward to further work by the Executive Board on elements of the new quota formula that can be improved before the formula is used again, and noted that this work should start before the 2009 Annual Meetings.